If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(x + 3y + 4z) = 0 (x * 2x + 3y * 2x + 4z * 2x) = 0 Reorder the terms: (6xy + 8xz + 2x2) = 0 (6xy + 8xz + 2x2) = 0 Solving 6xy + 8xz + 2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2x'. 2x(3y + 4z + x) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(3y + 4z + x)' equal to zero and attempt to solve: Simplifying 3y + 4z + x = 0 Reorder the terms: x + 3y + 4z = 0 Solving x + 3y + 4z = 0 Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. x + 3y + -3y + 4z = 0 + -3y Combine like terms: 3y + -3y = 0 x + 0 + 4z = 0 + -3y x + 4z = 0 + -3y Remove the zero: x + 4z = -3y Add '-4z' to each side of the equation. x + 4z + -4z = -3y + -4z Combine like terms: 4z + -4z = 0 x + 0 = -3y + -4z x = -3y + -4z Simplifying x = -3y + -4zSolution
x = {0, -3y + -4z}
| 11*1.86-12= | | X^2+1x+.25=0 | | -31-9x=-6x+32 | | y-x^2+6x=k | | 5x-10+(-9)=-7+7x | | 8x+11=3x-19 | | -14b-5=12b+8 | | -20-6x=6-4x | | 4x+4(x-1)+2(x-3)=0 | | 21=-27+6x | | -3(9+a)=33 | | 8+11a=-234 | | B(3b-1)= | | 13m-7-10(3m+10)= | | 12x-118=138-4x | | -5(3x-9)+7=-15x+52 | | 6x+10=5(-2x+-4) | | 144+2x=64+22x | | 11111111111111116=5x | | 144+2x=64+22 | | -159-5x=12x+96 | | x+4(x+1)-2(x-3)=1 | | 6(3-t)=-27 | | -7a+9=49 | | -5=x-17 | | -185.00+35.00x=070.00-50.00x | | 5*2=9 | | 8r+7-6r-5= | | 4x+3(x-4)-(x+2)=6 | | 5p-25=2 | | F(4)=18x+14 | | 9s+4=148 |